Deliberative Kommentarqualität auf Social Media: Einflussfaktoren und die Rolle von KI-Wortfiltern - Wolleschensky, Johanna (Communicatio socialis, 2025)
Comment sections offer great democratic potential but are often criticized for the low quality of the discussions they generate. Against that backdrop, this study examines 4,062 social media comments to determine which factors influence the deliberative quality of comments and what contribution AI word filters can make in this regard. The analysis shows that topics, news factors, and platforms can influence comment quality. However, a stricter word filter has no measurable influence. The results suggest that moderation by AI word filters alone is not sufficient to improve the quality of discussion in the long term but should serve as a supplement to human moderation.